Muslim AmeRícans: Puerto Rican Muslims in the USA and the Need for More Cosmopolitan Frames of Analysis in the Study of Islam and Muslim Communities in the Americas - Chitwood, Ken (International journal of Latin American religions, 2019)
This article seeks to contribute to the study of Islam and Muslims in Latin America and the Caribbean by considering broader geographies in the Americas and viewing these communitiesin light of hemispheric dynamics of movement, encounter, interaction, and exchange. This article seeks to do so in two distinct ways: first, by presenting the narratives of Puerto Rican Muslims' everyday cosmopolitan lives in the USA in the context of movement, migration, transnational connection, and solidarity between and across borders and boundaries in the Americas; second, by suggesting that telling such transnational tales not only expands our view of what it means to be Muslim in the Americas, but also that it helps broaden our understanding of what it means to be Muslim in a cosmopolitan age. To do so, this chapter highlights four different narratives from among Puerto Rican Muslims in the USA as a way to situate their significance in the narrative of Islam and Muslim communities in the Americas as a whole: first, that of Youssef Ali Abdullah in Staten Island; second, Danny Khalil "al-Portorikani" in Yonkers; third, the impact of Hurricane Maria in 2017 on the Puerto Rican Muslim community in the New York and New Jersey area as a whole; and fourth, through the story of the founding of Alianza Islámica in Spanish Harlem in the 1980s. These narratives were sourced during my fieldwork in New York City in summer 2016 and fall 2017 and as part of a broader ethnographic research project with Puerto Rican Muslims in the USA, in Puerto Rico, and online.